As-synthesized oleic amido propyl betaine surfactant mixture and the effect on the crude oil-seawater interfacial tension - Wazir, N.A. (MDPI AG, 2020)
As-synthesized oleic amido propyl betaine surfactant mixture was developed through a slight modification of a conventional two-step betaine synthesis process of amidation and quaternization reactions. This method is a "direct formulating through synthesis" to achieve a targeted interfacial property (interfacial tension or IFT) of the as-synthesized surfactant. Oil-water IFT was measured in the crude oil-seawater system at 96 °C. The result showed that the as-synthesized surfactant was able to reduce crude oil-seawater IFT to the ultra-low level (<0.01 mN/m). As the finding emerged, the investigation was conducted to identify the elements that would bring the characteristic of ultra-low IFT. The characterization of the surfactant using FTIR, TG-IR, and HPLC suggested that unreacted materials associated with the surfactant remained, such as the carryover of a fatty amide from the intermediate process, residues of N, N trimethylene dimethylamine and sodium chloride as a by-product, and the important newly formed sodium oleate compound that was inadvertently generated via the reaction. The performance of the as-synthesized in seawater condition has been verified and the surface tension plot shows the lowest surface tension point at 0.05 wt. concentration before developing a plateau region at higher surfactant concentration, indicating that the formation of surfactant micelles has been interrupted by the presence of other components in the solution. The dynamic IFT test performed on the as-synthesized product revealed that it was still able to reduce the crude oil-seawater IFT to an ultra-low level, despite the multiple undesirable components in the surfactant. IFT as low as 3.4 x 10-4 mN/m for the specific seawater and crude oil composition was obtained at a temperature of 96 °C. © 2020 by the authors.